2022
DOI: 10.1186/s12883-022-02909-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between miRNA-145 and miRNA-155 expression in peripheral blood mononuclear cells of patients with multiple sclerosis: a case-control study

Abstract: Introduction MicroRNAs (miR or miRNA) are short regulatory RNAs, which modulate post-transcriptional gene expression. Dysregulation of these molecules contributes to pathogenicity of autoimmune disorders, such as multiple sclerosis (MS). Aims This study was conducted to investigate changed expression pattern of miRNA-145 and miRNA-155 in MS. Methods We collected blood samples of 75 patients with relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Both studies where discrepancies between miR-155 or SARAF expression in regard to the present study were observed were also performed on particular Iranian and Bahraini populations [ 22 , 43 ]. In the later study, the authors also pointed to particular Middle East and Gulf region populations and stated that further studies are required in order to elucidate the role of the SARAF gene in multiple sclerosis [ 43 ], depicting an awareness of genetic heterogeneity between different populations.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Both studies where discrepancies between miR-155 or SARAF expression in regard to the present study were observed were also performed on particular Iranian and Bahraini populations [ 22 , 43 ]. In the later study, the authors also pointed to particular Middle East and Gulf region populations and stated that further studies are required in order to elucidate the role of the SARAF gene in multiple sclerosis [ 43 ], depicting an awareness of genetic heterogeneity between different populations.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, it is shown that the inhibition of miR-155 expression is effective in preventing processes that are involved in the pathophysiology of multiple sclerosis [ 16 ]. A recent study also suggests that miR-155 expression, together with miR-145 expression, in PBMCs is associated with RRMS [ 22 ]. However, the later study also demonstrated contradictory findings that higher levels of miR-155 and miR-145 expression was observed in controls and not RRMS patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have profiled miRNAs in blood, other biological fluids, or cells in MS, with some miRNAs differing between MS and healthy controls, MS subtypes, or with outcomes such as MRI lesions, disability, or response to therapy [138,[140][141][142][143]. Though there are conflicting results and lack of replication in the miRNA biomarker literature, several miRNAs with known roles in inflammatory signaling, including regulation of lymphocyte subsets, have been identified in multiple MS studies, including miR-145, miR-155, and miR-92a [140,[143][144][145][146][147][148]. The roles of miRNAs as biomarkers and potential therapies in MS are reviewed in detail elsewhere [149,150].…”
Section: Micro Rnasmentioning
confidence: 99%